Use of tyrosine kinase inhibitor by patients with chronic myeloid leukemia at a public hematology institution in the state of Amazonas, Brazil - Andreia D. MENEZES; Nelson A. FRAIJI (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objectives: To evaluate the conditions of use of tyrosine kinase inhibitors and adherence by patients with chronic myeloid leukemia treated at a public hematology institution. Methods: This was an observational and cross-sectional study carried out from December 2015 to April 2016. Data collection was carried out through interviews with standardized questionnaires that assessed the socioeconomic and demographic profile, drug therapy and by the Morisky-Green test that assessed the green adherence. Patients over 18 years old who had been using one of the tyrosine kinase inhibitors for more than one month were included; imatinib, dasatinib or nilotinib and who signed the informed consert form, agreement to participate in study. Descriptive statistical analysis and chi-square test with Yates correction were performed. Results: 63 patients were interviewed, with a mean age of 50 years with a standard deviation of 15.95. being 60% men. As for knowledge about the aspects related to the use of inhibitors: 95.2% took at the right time, 93.7% did not use other medications concomitantly, 63.5% kept it in an appropriate place and 97% of the patients received prior guidance from the doctor about the use. As for information about treatment, 90.5% knew the purpose of taking the medication, 60% did not know the time of use, 83% did not know what would happen if they stopped taking it and 73% believed they could stop the treatment at some point. Adherence to treatment was identified 46% of patients. Conclusion: No statistically significant differences were found between having or not adherence, when compared with the studied variables.